2010
DOI: 10.1063/1.3291103
|View full text |Cite
|
Sign up to set email alerts
|

Thickness effect on the band gap and optical properties of germanium thin films

Abstract: The band gap and optical properties ͑dielectric functions and optical constants͒ of Ge thin films with various thicknesses below 50 nm, which were synthesized with electron beam evaporation technique, have been determined using spectroscopic ellipsometry and UV-visible spectrophotometry. The optical properties are well described with the Forouhi-Bloomer model. Both the band gap and optical properties show a strong dependence on the film thickness. For film thickness smaller than ϳ10 nm, a band gap expansion is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(48 citation statements)
references
References 23 publications
3
42
0
3
Order By: Relevance
“…10 illustrates that refractive indices increase with increasing thickness. Such refractive index increases with increasing thickness for Zn 0.995 Ni 0.005 S nanocrystalline thin film is in good agreement with thickness effect reported for other materials [32,33].…”
Section: Refractive Index Dispersion Of Zn 1−x Ni X S Nanocrystallinesupporting
confidence: 91%
“…10 illustrates that refractive indices increase with increasing thickness. Such refractive index increases with increasing thickness for Zn 0.995 Ni 0.005 S nanocrystalline thin film is in good agreement with thickness effect reported for other materials [32,33].…”
Section: Refractive Index Dispersion Of Zn 1−x Ni X S Nanocrystallinesupporting
confidence: 91%
“…Further, the data presented in Table 2 confirmed that the optical band gap decreased with the increase in VO-MO film thickness. These observations could be explained in terms of the well recognized quantum confinement or size effect354354.…”
Section: Resultsmentioning
confidence: 92%
“…It has been reported that when the thickness of ZnO and Ge thin films scales down to 20 nm, the ultrathin films exhibit an expansion of bandgap and a reduction of dielectric function due to the quantum confinement effect. 10,13 As shown in Fig. 2a for the IGZO thin films thinner than ∼20 nm, the ultrathin films exhibit a blueshift in both real and imaginary parts of dielectric function with decreasing film thickness.…”
Section: Ellipsometric Modelingmentioning
confidence: 89%
“…It has been shown that thickness dependence of band gaps of ultrathin amorphous materials can be described by the ODQC effect. 13,16 Figure 4 shows the bandgap energy of the IGZO thin films yielded from the SE modelling. A significant dependence of bandgap on film thickness is observed.…”
Section: Ellipsometric Modelingmentioning
confidence: 99%